(untitled) (Philology, 2026)
In recent years, with the deepening of cooperation between China and Bulgaria, the joint efforts in the field of education have also increased. The collaboration in education and the mutual exchange between Chinese and Bulgarian students are also prosperous. However, this process is accompanied by many language problems that learners face. This article presents the results of questionnaires, comparative analysis and personal observations of the foreign language learning situation of Chinese and Bulgarian university students. The main factors for the difficulties in the process of education are related to the differences between Chinese and Bulgarian in certain levels: phonetics, verb morphology, tense system and writing. These factors pose considerable challenges for Chinese and Bulgarian students. In the article there are comparison and analyses the results of the two questionnaire surveys conducted with representatives of both groups. The aim is to be provided a deeper, intercultural observation and research of the challenges in learning and to give recommendations that could be used as an authentic basis for future teaching and learning Chinese and Bulgarian.